2007
DOI: 10.1080/10241220701697924
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic study of adsorption in polysaccharide metabolism

Abstract: Starch metabolism due to adsorption of enzyme amylase on the starch substrate is outlined briefly. To explore the necessary conditions required for effective adsorption in biological media, ultrasonic techniques have been applied to elucidate the structural variations and component destruction in the considered systems. The ability of the enzyme amylase to break the linkages in two different polysaccharide substrates was determined from the observed ultrasonic data, which highlights the deciding factors of met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The observed decreases values of V f in system 1 are due to close association between solute and solvent molecules than system 2. Thus it is observed that in system 2 show different results from those of other three components 13 . Thus, a progressive decrease in free volume and increase in internal pressure in water-dioxane mixtures clearly indicates the existence of ion-solvent interaction, due to which the structural arrangement is considerably affected.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The observed decreases values of V f in system 1 are due to close association between solute and solvent molecules than system 2. Thus it is observed that in system 2 show different results from those of other three components 13 . Thus, a progressive decrease in free volume and increase in internal pressure in water-dioxane mixtures clearly indicates the existence of ion-solvent interaction, due to which the structural arrangement is considerably affected.…”
Section: Resultsmentioning
confidence: 80%
“…Ultrasonic technique has been adequately employed to investigate the properties of any substance to understand the nature of molecular interactions in pure liquid 1 , liquid mixtures [2][3][4][5] and ionic interactions in electrolytic solutions 6,7 . Though the molecular interactions studies can be best carried out through spectroscopic methods 8,9 the other non spectroscopic techniques such as dielectric 10 magnetic 11 ultrasonic velocity and viscosity [12][13][14] measurements have been widely used in field of interactions and structural aspect evaluations studies. In the present work an attempt has been made to investigate the behaviour of binary solutions of water in 1,4-dioxane and acetone with regard to adiabatic compressibility, intermolecular free length and specific acoustic impedance from ultrasonic measurements at 303 K.…”
Section: Introductionmentioning
confidence: 99%
“…Calculation of thermo-acoustical parameters: As stated earlier, the chosen thermo acoustical parameters are calculated using the following standard relations (Swain and Priyadarshini 2010, Velusamy et al 2007,Walter et al 1995 Ramanathan 2010, Kadi et al 2006) β=…”
Section: Methodsmentioning
confidence: 99%
“…The chosen thermo acoustical parameters are calculated using the following standard relations (Velusamy and Palaniappan 2013;Velusamy et al 2007;Vanathi et al 2019;Ravichandran and Ramanathan 2010;Kadi et al 2006).…”
Section: Calculated Parametersmentioning
confidence: 99%